Method for manufacturing polishing pad and polished product

JP7640673B2Active Publication Date: 2025-03-05FUJIBO HLDG

Patent Information

Application Number
JP2023508174
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-03-05
Estimated Expiration
2041-03-22

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、スクラッチの発生を低減することのできる研磨パッド及び研磨加工物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640673000002
    Figure 0007640673000002
  • Figure 0007640673000003
    Figure 0007640673000003
  • Figure 0007640673000001
    Figure 0007640673000001
Patent Text Reader

Abstract

This polishing pad comprises a polyurethane sheet as a polishing layer, the polyurethane sheet being such that the ratio (E'B40 / E'T40) of the 40°C storage elastic modulus E'B40 in a dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz to the 40°C storage elastic modulus E'T40 in a dynamic viscoelasticity measurement performed under tension mode conditions at a frequency of 1.6 Hz is 0.60-1.60.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a polishing pad and a polished workpiece. [Background technology]

[0002] The surfaces (machined surfaces) of materials such as semiconductor devices and electronic components, particularly thin substrates (workpieces) such as Si substrates (silicon wafers), hard disk substrates, glass, and LCD (liquid crystal display) substrates, are chemically mechanically polished using a polishing pad and a polishing slurry.

[0003] As polishing pads used in such polishing processes, for example, polishing pads having a polishing layer with an E' ratio at 30°C to 90°C of about 1 to 3.6 for the purpose of reducing dishing (Patent Document 1) are used, and polishing pads having a polishing layer made of a polymer material with a porosity of 0.1 volume %, a KEL energy loss coefficient of 385 to 750 l / Pa at 40°C and 1 rad / sec, and an elastic modulus E' of 100 to 400 MPa at 40°C and 1 rad / sec are used for the purpose of achieving both planarization performance and low defect performance rate (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2004-507076 [Patent Document 2] JP 2005-136400 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, it has been found that when the polishing pads described in Patent Documents 1 and 2 are used, the surface quality of the polished object obtained cannot be said to be high, and for example scratches and the like occur.

[0006] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a polishing pad and a method for manufacturing a polished product that can reduce the occurrence of scratches. [Means for solving the problem]

[0007] As a result of intensive research into solving the above problems, the inventors discovered that the above problems can be solved by using as a polishing layer a polyurethane sheet that has a storage modulus value within a predetermined range when dynamic viscoelasticity measurements are performed in tensile mode and bending mode, and thus completed the present invention.

[0008] That is, the present invention is as follows. [1] A polyurethane sheet is provided as the polishing layer, The polyurethane sheet has a storage modulus E' at 40°C in dynamic viscoelasticity measurement performed under tensile mode conditions at a frequency of 1.6 Hz. T40 Storage modulus E' at 40°C in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz B40 The ratio (E' B40 / E' T40 ) is 0.60 to 1.60, Polishing pad. [2] The storage elastic modulus E' B40 But 1.50×10 8 ~4.50×10 8 Pa, The polishing pad described in [1]. [3] The storage elastic modulus E' T40 But 1.50×10 8 ~4.50×10 8 Pa, The polishing pad according to [1] or [2]. [4] The polyurethane sheet has a storage modulus E' at 50°C in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz. B50 Storage modulus E' at 30°C B30 The ratio (E'B30 / E' B50 ) is between 1.00 and 2.60. The polishing pad according to any one of [1] to [3]. [5] The polyurethane sheet contains a polyurethane resin and hollow fine particles dispersed in the polyurethane resin. The polishing pad according to any one of [1] to [4]. [6] The hollow fine particles have an average particle size of 30 μm or less. The polishing pad according to [5]. [7] A polishing step of polishing an object to be polished using the polishing pad according to any one of [1] to [6] in the presence of a polishing slurry. A method for manufacturing polished workpieces. Effect of the Invention

[0009] According to the present invention, it is possible to provide a polishing pad and a method for manufacturing a polished product that can reduce the occurrence of scratches. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a diagram showing the results of dynamic viscoelasticity measurement in Example 1. [Diagram 2] FIG. 1 is a diagram showing the results of dynamic viscoelasticity measurement in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, we will explain in detail the embodiment of the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0012] [Polishing pad] The polishing pad of this embodiment includes a polyurethane sheet as a polishing layer, and the polyurethane sheet has a storage modulus E' at 40° C. in dynamic viscoelasticity measurement performed under tensile mode conditions at a frequency of 1.6 Hz.T40 Storage modulus E' at 40°C in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz B40 The ratio (E' B40 / E' T40 ) is 0.60 to 1.60.

[0013] The storage modulus E' is an index showing the elastic component of the substance to be measured under the measurement conditions. Before polishing the object to be polished with the polishing pad, a dressing process is performed to adjust the flatness and surface roughness of the polishing surface. In the dressing process, a vertical force (dressing pressure) is applied to press the dresser against the polishing pad, and a horizontal force (rotational force) is applied to rub the dresser against the polishing pad. In addition, in the polishing process in which the object to be polished and the polishing pad come into contact with each other, a vertical force (polishing pressure) is applied to press the polishing pad against the object to be polished, and a horizontal force (rotational force) is applied to rub the polishing pad against the object to be polished. At this time, the polishing pad to which these two types of forces are applied follows the dresser and the object to be polished to a certain extent, thereby obtaining a polished product with excellent surface quality. For this reason, in this embodiment, the occurrence of scratches is suppressed by specifying the ratio of the storage modulus E' obtained when dynamic viscoelasticity measurement is performed in the tensile mode and the bending mode. Although it is said that the results of dynamic viscoelasticity measurements in the tensile mode and bending mode are roughly consistent, they at least show different behaviors in a polishing pad.

[0014] From the above viewpoint, in this embodiment, the storage modulus E' at 40° C. in dynamic viscoelasticity measurement performed under tensile mode conditions at a frequency of 1.6 Hz is T40 Storage modulus E' at 40°C in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz B40 The ratio (E' B40 / E' T40 ) is the index. B40 / E' T40 The ratio (E') is 0.60 to 1.60, preferably 0.70 to 1.40, more preferably 0.75 to 1.20, and further preferably 0.80 to 1.00. B40 / E'T40 ) is within the above range, in particular, the ratio (E' B40 / E' T40 ) is 0.60 or more, the polishing pad can more effectively follow the dresser against vertical and horizontal forces, improving the condition of the polishing surface and suppressing the occurrence of scratches. The reason for this is not particularly limited, but it is considered that the polishing pad can more effectively follow the dresser against vertical and horizontal forces when the tensile storage modulus responding to horizontal forces and the bending storage modulus responding to vertical forces and following the surface of the polished object are in the above ranges. However, the reason for suppressing the occurrence of scratches is not limited to the above.

[0015] Also, E' B40 is preferably 1.50 x 10 8 ~4.50×10 8 Pa, preferably 1.75×10 8 ~4.10×10 8 Pa, preferably 2.00×10 8 ~3.70×10 8 Pa. E' B40 When the surface roughness is within the above range, the polishing pad more effectively follows the dresser against a force in the vertical direction, improving the condition of the polished surface and further suppressing the occurrence of scratches.

[0016] E' T40 is preferably 1.50 x 10 8 ~4.50×10 8 Pa, preferably 2.00×10 8 ~4.20×10 8 Pa, preferably 2.30×10 8 ~3.90×10 8 Pa. E' T40 When the surface roughness is within the above range, the polishing pad more effectively follows the dresser against horizontal forces, improving the condition of the polished surface and further suppressing the occurrence of scratches.

[0017] Since the temperature of the polishing pad in the polishing process is often about 40° C., in this embodiment, the ratio of the storage modulus in bending mode to that in tension mode at 40° C. is specified. In relation to this, the tendency of the storage modulus in bending mode may be further specified. Specifically, the storage modulus E' at 50° C. in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz is B50 Storage modulus E' at 30°C B30 The ratio (E' B30 / E' B50 The ratio (E') is preferably 1.00 to 2.60, more preferably 1.20 to 2.30, and further preferably 1.30 to 2.00. B30 / E' B50 Since the storage modulus change rate at 30 to 50°C is small, the ratio of the storage modulus in bending mode to that in tension mode (E' B40 / E' T40 ) tends to satisfy the prescribed range. Therefore, in the polishing process, the polishing pad more effectively follows the dresser against vertical and horizontal forces, improving the condition of the polished surface and further suppressing the occurrence of scratches.

[0018] In addition, E' B30 is preferably 2.50 x 10 8 ~5.50×10 8 Pa, preferably 2.60×10 8 ~5.00×10 8 Pa, preferably 2.70×10 8 ~4.50×10 8 Pa. Also, E' B50 is preferably 1.00 x 10 8 ~3.50×10 8 Pa, preferably 1.25×10 8 ~3.20×10 8 Pa, preferably 1.50×10 8 ~2.90×10 8 Pa. E' B30 and / or E' B50 When the content is within the above range, the occurrence of scratches tends to be further suppressed.

[0019] The dynamic viscoelasticity measurement in this embodiment can be carried out according to conventional methods in bending mode and tension mode, and the other conditions are not particularly limited, but can be measured under the conditions described in the examples.

[0020] (Polyurethane sheet) The polishing layer having the above characteristics is a polyurethane sheet. The polyurethane resin constituting the polyurethane sheet is not particularly limited, but for example, polyester polyurethane resin, polyether polyurethane resin, and polycarbonate polyurethane resin can be mentioned. Such polyurethane resin is not particularly limited as long as it is a reaction product of a urethane prepolymer and a curing agent, and various known ones can be applied. These may be used alone or in combination of two or more.

[0021] (Urethane prepolymer) The urethane prepolymer is not particularly limited, and a reaction product of a polyisocyanate compound and a polyol compound, or a commercially available urethane prepolymer can be appropriately used.

[0022] The polyisocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups in the molecule, and examples thereof include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-tolylene diisocyanate, naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate, 4,4'-methylene-bis(cyclohexyl isocyanate), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyldiphenyl diisocyanate, 4,4'-dimethyl ... Examples of the diisocyanate include phenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, and ethylidine diisothiocyanate.

[0023] Among these, 2,6-tolylene diisocyanate, 2,4-tolylene diisocyanate, and diphenylmethane-4,4'-diisocyanate are preferred, and 2,6-tolylene diisocyanate and 2,4-tolylene diisocyanate are more preferred. The polyisocyanate compounds may be used alone or in combination of two or more kinds.

[0024] The polyol compound is not particularly limited as long as it is a compound having two or more hydroxyl groups in the molecule, and examples thereof include diol compounds such as ethylene glycol, diethylene glycol, butylene glycol, etc.; triol compounds; polyether polyol compounds such as polypropylene glycol, poly(oxytetramethylene) glycol, etc.; polyester polyol compounds such as the reaction product of ethylene glycol and adipic acid, or the reaction product of butylene glycol and adipic acid; polycarbonate polyol compounds, polycaprolactone polyol compounds; and trifunctional propylene glycol with added ethylene oxide.

[0025] Among these, poly(oxytetramethylene) glycol, polypropylene glycol, and diethylene glycol are preferred, and poly(oxytetramethylene) glycol is more preferred. The polyol compounds may be used alone or in combination of two or more.

[0026] The polyol compound may be a combination of a high molecular weight polyol such as poly(oxytetramethylene) glycol or polypropylene glycol and a low molecular weight polyol such as diethylene glycol. The number average molecular weight of the high molecular weight polyol is preferably 300 to 2000, more preferably 400 to 1750, and further preferably 500 to 1500. The high molecular weight polyol may contain two or more types of polyols having different number average molecular weights.

[0027] The NCO equivalent of the urethane prepolymer is preferably 300 to 700, more preferably 350 to 600, and further preferably 400 to 500. The "NCO equivalent" is calculated by "(parts by mass of polyisocyanate compound + parts by mass of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × parts by mass of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × parts by mass of polyol compound / molecular weight of polyol compound)]" and is a numerical value indicating the molecular weight of the urethane prepolymer per NCO group.

[0028] (hardening agent) The curing agent is not particularly limited, but examples thereof include polyhydric amine compounds and polyhydric alcohol compounds. The curing agent may be used alone or in combination of two or more kinds.

[0029] The polyamine compound is not particularly limited, and examples thereof include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis[3 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethylethylene bis-4-aminobenzoate, and polytetramethylene oxide-di-p-aminobenzoate.

[0030] The polyhydric alcohol compound is not particularly limited, and examples thereof include ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, Examples of the copolymer include glycol, 3-methyl-4,3-pentanediol, 3-methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol.

[0031] The polyvalent amine compound may have a hydroxyl group, and examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, and di-2-hydroxypropylethylenediamine.

[0032] Among these, the polyvalent amine compound is preferably a diamine compound, and more preferably 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA). Commercially available MOCA products include, for example, PANDEX E (manufactured by DIC Corporation) and Iharakyuamine MT (manufactured by Kumiai Chemical Co., Ltd.). The curing agent may be used alone or in combination of two or more kinds.

[0033] The amount of the curing agent added is preferably 10 to 60 parts by mass, more preferably 20 to 50 parts by mass, and even more preferably 20 to 40 parts by mass, based on 100 parts by mass of the urethane prepolymer.

[0034] The storage modulus in bending mode and tensile mode can be adjusted by the molecular weight (degree of polymerization) of the urethane prepolymer and the combination of the urethane prepolymer and the curing agent. From this viewpoint, for example, the R value, which is the equivalent ratio of the active hydrogen groups (amino groups and hydroxyl groups) present in the curing agent to the isocyanate groups present at the terminals of the isocyanate group-containing compound as the urethane prepolymer, can be used as an index. The R value is preferably 0.70 to 1.30, more preferably 0.75 to 1.20, even more preferably 0.80 to 1.10, still more preferably 0.80 to 1.00, and even more preferably 0.85 to 0.95.

[0035] (Air bubbles) The polyurethane sheet is preferably a foamed polyurethane sheet having bubbles. The bubbles of the foamed polyurethane sheet are classified into closed bubbles, in which a plurality of bubbles exist independently, and open bubbles, in which a plurality of bubbles are connected by communicating holes, depending on the form of the bubbles. Among these, the polyurethane sheet of the present embodiment preferably has closed bubbles, and is more preferably a polyurethane sheet containing a polyurethane resin and hollow fine particles dispersed in the polyurethane resin. By using hollow fine particles, it tends to be easier to adjust the storage modulus in bending mode and tensile mode.

[0036] The polyurethane sheet having closed cells can be produced by using hollow particles having an outer shell and a hollow interior. The hollow particles to be used may be commercially available or may be synthesized by a conventional method.

[0037] The material of the shell of the hollow microparticles is not particularly limited, but examples thereof include polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride, and organic silicone resins, as well as copolymers of two or more of the monomers constituting these resins. In addition, examples of commercially available hollow microparticles include, but are not limited to, the Expancel series (trade name, manufactured by Akzo Nobel), Matsumoto Microsphere (trade name, manufactured by Matsumoto Oil Co., Ltd.), and the like.

[0038] The shape of the hollow fine particles in the polyurethane sheet is not particularly limited, and may be, for example, spherical or approximately spherical. The average particle size of the hollow fine particles is preferably 30 μm or less, more preferably 25 μm or less, even more preferably 20 μm or less, even more preferably 15 μm or less, and even more preferably 10 μm or less. The average particle size of the hollow fine particles is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 4 μm or more. The storage modulus of the bending mode and the tensile mode can also be adjusted by using such hollow fine particles. The average particle size can be measured by a laser diffraction type particle size distribution measuring device (for example, Mastersizer-2000, manufactured by Spectris Co., Ltd.). By having the average particle size of the hollow fine particles within the above range, the effect of the size of the bubbles formed by the hollow fine particles on the storage modulus can be reduced, and the storage modulus of the bending and tensile modes can be adjusted to a desired range. In this embodiment, the average particle size means the median diameter based on volume.

[0039] The hollow particles include expanded types that are already expanded and unexpanded types that are not expanded, but unexpanded types are preferred. By using unexpanded hollow particles, small bubbles formed in the polyurethane sheet are dispersed, and the bending and tensile storage moduli can be adjusted to the desired range.

[0040] The amount of hollow fine particles added is preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, and further preferably 1 to 4 parts by mass, based on 100 parts by mass of the urethane prepolymer. By adjusting the amount of hollow fine particles added within the above range, the storage modulus in bending mode and tensile mode can also be adjusted.

[0041] (Other Ingredients) In addition to the above components, conventionally used blowing agents may be used in combination with the hollow fine particles within the range that does not impair the effects of the present invention, and a gas that is non-reactive with each component may be blown in during the mixing step described below. Examples of the blowing agent include water and blowing agents that are mainly composed of a hydrocarbon having 5 or 6 carbon atoms. Examples of the hydrocarbon include chain hydrocarbons such as n-pentane and n-hexane, and alicyclic hydrocarbons such as cyclopentane and cyclohexane. In addition to the above components, known foam stabilizers, flame retardants, colorants, plasticizers, etc. may be added.

[0042] (Method of manufacturing polyurethane sheet) The method for producing a polyurethane sheet is not particularly limited, but may include, for example, a method having a reaction step of reacting a urethane prepolymer with a curing agent in the presence of hollow fine particles to obtain a polyurethane resin block, and a molding step of cutting out a sheet from the obtained polyurethane resin block. Each step will be described in detail below.

[0043] (Reaction process) In the reaction step, the urethane prepolymer and the curing agent are fed into a mixer and stirred and mixed to carry out the reaction. When hollow microparticles are used, a polyurethane resin block incorporating the hollow microparticles can be obtained by mixing the urethane prepolymer, the curing agent, and the hollow microparticles. There is no particular restriction on the order in which the components are mixed, but it is preferable to mix the urethane prepolymer and the hollow microparticles first and then feed the curing agent into the mixer.

[0044] In this embodiment, from the viewpoint of adjusting the storage modulus in bending mode and tension mode, it is desirable to reduce the bubble diameter in the polyurethane sheet, and the diameter of hollow fine particles when used. Therefore, in the reaction between the urethane prepolymer and the curing agent, it is preferable to mix them under conditions that do not cause the hollow fine particles to expand.

[0045] One such method is, for example, to mix hollow microparticles and a urethane prepolymer in a first tank under conditions in which relatively little heat is applied, and then to mix a curing agent separately in a second liquid tank, and then to add the hollow microparticles and the urethane prepolymer from the first tank and the curing agent from the second tank to a mixer and mix them.

[0046] More specifically, the temperature of the first liquid tank is preferably 30 to 80° C., more preferably 35 to 70° C., and further preferably 40 to 65° C. This can suppress the expansion of the hollow fine particles.

[0047] Next, the mixed liquid prepared as above is poured into a mold preheated to 30 to 100°C, and heated at about 100 to 150°C for about 10 minutes to 5 hours to harden it, forming a polyurethane resin block. At this time, the urethane prepolymer reacts with the hardener, and the mixed liquid hardens in a state in which air bubbles and / or hollow fine particles are dispersed in the polyurethane resin. This forms a polyurethane resin block containing a large number of roughly spherical air bubbles.

[0048] (molding process) The resulting polyurethane resin block is then sliced ​​into sheets to form polyurethane sheets. By slicing, openings are provided on the surface of the sheet. At this time, aging may be performed at 30 to 150°C for about 1 to 24 hours to form openings on the surface of the polishing layer that is highly resistant to wear and less prone to clogging.

[0049] The polishing layer having the polyurethane sheet thus obtained is then attached with a double-sided tape on the surface opposite to the polishing surface of the polishing layer, and cut into a predetermined shape, preferably a disk shape, to complete the polishing pad of this embodiment. There is no particular restriction on the double-sided tape, and any double-sided tape known in the art can be selected and used.

[0050] In addition, the polishing pad of this embodiment may be a single-layer structure consisting of only a polishing layer, or may be a multi-layer structure in which other layers (lower layer, support layer) are attached to the surface opposite to the polishing surface of the polishing layer. The properties of the other layers are not particularly limited, and if a layer softer than the polishing layer is attached to the surface opposite to the polishing layer, the polishing flatness is further improved. On the other hand, if a layer harder than the polishing layer is attached to the surface opposite to the polishing layer, the polishing rate is further improved.

[0051] In the case of a multi-layer structure, the layers may be bonded and fixed together, if necessary, under pressure, using double-sided tape, adhesive, etc. There are no particular limitations on the double-sided tape or adhesive used in this case, and any double-sided tape or adhesive known in the art may be selected and used.

[0052] Furthermore, in the polishing pad of this embodiment, if necessary, the surface and / or back surface of the polishing layer may be subjected to grinding, groove processing, embossing, or hole processing (punching) on ​​the surface, the substrate and / or adhesive layer may be attached to the polishing layer, and a light transmitting portion may be provided. There is no particular limitation on the method of grinding, and grinding can be performed by a known method. Specifically, grinding with sandpaper can be mentioned. There is no particular limitation on the shape of the groove processing and embossing, and examples thereof include a lattice type, a concentric circle type, and a radial type.

[0053] [Method for manufacturing polished product] The method for producing the polished product of this embodiment includes a polishing step of polishing a workpiece using the polishing pad in the presence of a polishing slurry to obtain a polished product. The polishing step may be primary polishing (rough polishing), finish polishing, or a combination of both. Among these, the polishing pad of this embodiment is preferably used for chemical mechanical polishing. Hereinafter, the method for producing the polished product of this embodiment will be described using chemical mechanical polishing as an example, but the method for producing the polished product of this embodiment is not limited to the following.

[0054] In this manufacturing method, the polishing slurry is supplied, and the holding platen and the polishing platen are rotated relative to each other while the object to be polished is pressed against the polishing pad by the holding platen, so that the processed surface of the object to be polished is polished by the polishing pad by chemical mechanical polishing (CMP). The holding platen and the polishing platen may rotate in the same direction at different rotation speeds, or in different directions. The object to be polished may be polished while moving (rotating) inside the frame during the polishing process.

[0055] The polishing slurry may contain water, chemical components such as an oxidizing agent such as hydrogen peroxide, additives, abrasive grains (polishing particles; e.g., SiC, SiO2, Al2O3, CeO2), etc. depending on the object to be polished and the polishing conditions.

[0056] The object to be polished is not particularly limited, but examples thereof include materials such as semiconductor devices and electronic components, particularly thin substrates (objects to be polished) such as Si substrates (silicon wafers), substrates for hard disks, glass and substrates for LCDs (liquid crystal displays). Among these, the method for manufacturing the polished object of the present embodiment can be suitably used as a method for manufacturing semiconductor devices having an oxide layer, a metal layer such as copper, etc. EXAMPLES

[0057] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0058] Example 1 2,4-tolylene diisocyanate, poly(oxytetramethylene) glycol (number average molecular weight 1000), poly(oxytetramethylene) glycol (number average molecular weight 650), and diethylene glycol were reacted to obtain 100 parts of a urethane prepolymer having an NCO equivalent of 455. The shell portion was made of an acrylonitrile-vinylidene chloride copolymer, and 2.7 parts of unexpanded hollow fine particles (average particle size 8.5 μm) in which isobutane gas was contained in the shell were added and mixed to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept at 60°C. In addition to the first liquid tank, 25.8 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (MOCA) were charged into a second liquid tank as a curing agent, mixed at 120°C, and further degassed under reduced pressure to obtain a curing agent melt. In addition, the above operating temperature was set in order to suppress the expansion of the hollow fine particles.

[0059] Next, the liquids in the first liquid tank and the second liquid tank were poured into a mixer equipped with two injection ports, and mixed and stirred to obtain a mixed liquid. At this time, the mixing ratio was adjusted so that the R value, which represents the equivalent ratio of the amino group and hydroxyl group in the curing agent to the isocyanate group at the end of the urethane prepolymer, was 0.90.

[0060] The resulting mixture was poured into a mold preheated to 80°C and cured at 80°C for 30 minutes. The resulting block-shaped molding was removed from the mold and cured at 120°C for 4 hours in an oven to obtain a urethane resin block. The resulting urethane resin block was allowed to cool to 25°C, and then heated again at 120°C for 5 hours in an oven, after which it was sliced ​​to obtain a polyurethane foam sheet. Double-sided tape was attached to the back of the resulting polyurethane sheet, and it was used as a polishing pad.

[0061] Comparative Example 1 As Comparative Example 1, a polishing pad manufactured by Nitta Haas Corporation (product name: IC1000) was prepared.

[0062] Example 2 2,4-tolylene diisocyanate, poly(oxytetramethylene) glycol (number average molecular weight 1000), poly(oxytetramethylene) glycol (number average molecular weight 650), and diethylene glycol were reacted to obtain 100 parts of a urethane prepolymer having an NCO equivalent of 420. The shell portion was made of an acrylonitrile-vinylidene chloride copolymer, and 2.5 parts of unexpanded hollow fine particles (average particle size 8.5 μm) in which isobutane gas was encapsulated in the shell were added and mixed to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept at 60°C. In addition to the first liquid tank, 28.3 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (MOCA) were charged into a second liquid tank as a curing agent, mixed at 120°C, and further degassed under reduced pressure to obtain a curing agent melt. The above operating temperature was set in order to suppress the expansion of the hollow fine particles. A polishing pad of Example 2 was produced in the same manner as in Example 1 except for the above-mentioned operations.

[0063] Example 3 100 parts of a urethane prepolymer having an NCO equivalent of 420, which is made by reacting 2,4-tolylene diisocyanate, poly(oxytetramethylene) glycol (number average molecular weight 1000), poly(oxytetramethylene) glycol (number average molecular weight 650), and diethylene glycol, was mixed with 4.9 parts of unexpanded hollow fine particles (average particle size 5.3 μm) in which the shell portion is made of an acrylonitrile-vinylidene chloride copolymer and in which isobutane gas is contained in the shell, to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept at 60°C. In addition to the first liquid tank, 27.8 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (MOCA) was charged into a second liquid tank as a curing agent, mixed at 120°C, and further degassed under reduced pressure to obtain a curing agent melt. In addition, the above operating temperature was set in order to suppress the expansion of the hollow fine particles. A polishing pad of Example 3 was produced in the same manner as in Example 1 except for the above-mentioned operations.

[0064] Example 4 2,4-tolylene diisocyanate, poly(oxytetramethylene) glycol (number average molecular weight 650), and diethylene glycol were reacted to form a urethane prepolymer having an NCO equivalent of 420. 2.8 parts of unexpanded hollow fine particles (average particle size 6.9 μm) in which the shell portion is made of an acrylonitrile-vinylidene chloride copolymer and isobutane gas is contained in the shell were added and mixed to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept at 60°C. In addition to the first liquid tank, 28.1 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylene bis-o-chloroaniline) (MOCA) were added to a second liquid tank as a curing agent, mixed at 120°C, and further degassed under reduced pressure to obtain a curing agent melt. The above operating temperature was set in order to suppress the expansion of the hollow fine particles. The polishing pad of Example 4 was produced in the same manner as in Example 1 except for the above operation.

[0065] Example 5 2,4-tolylene diisocyanate, poly(oxytetramethylene) glycol (number average molecular weight 650), and diethylene glycol were reacted to form a urethane prepolymer having an NCO equivalent of 440. 2.9 parts of unexpanded hollow fine particles (average particle size 6.9 μm) in which the shell portion is made of an acrylonitrile-vinylidene chloride copolymer and isobutane gas is contained in the shell were added and mixed to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept warm at 60°C. In addition to the first liquid tank, 26.7 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylene bis-o-chloroaniline) (MOCA) were charged into a second liquid tank as a curing agent, mixed at 120°C, and further degassed under reduced pressure to obtain a curing agent melt. The above operating temperature was set in order to suppress the expansion of the hollow fine particles. The polishing pad of Example 5 was produced in the same manner as in Example 1 except for the above operation.

[0066] Example 6 100 parts of urethane prepolymer with an NCO equivalent of 500, which is made by reacting 2,4-tolylene diisocyanate, polypropylene glycol (number average molecular weight 100), and diethylene glycol, were mixed with 2.5 parts of expanded hollow fine particles (average particle size 20 μm) in which the shell portion is made of acrylonitrile-vinylidene chloride copolymer and isobutane gas is contained in the shell, to obtain a urethane prepolymer mixed liquid. The obtained urethane prepolymer mixed liquid was charged into a first liquid tank and kept warm at 60 ° C. In addition, 23.1 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylene bis-o-chloroaniline) (MOCA) were charged into a second liquid tank as a curing agent separately from the first liquid tank, mixed at 120 ° C, and further degassed under reduced pressure to obtain a curing agent melt. The polishing pad of Example 6 was produced in the same manner as in Example 1 except for the above operation.

[0067] [Dynamic viscoelasticity measurement] (Tension mode) Dynamic viscoelasticity measurements were performed on polyurethane sheets under the following conditions. A polyurethane sheet was kept in a thermohygrostat at a temperature of 23°C (±2°C) and a relative humidity of 50% (±5%) for 40 hours to obtain a dry polyurethane sheet as a sample, and dynamic viscoelasticity measurements were performed in tension mode under normal atmospheric conditions (dry state). The measurement conditions for tension mode are as follows: (Measurement conditions) Measurement device: RSA3 (manufactured by TA Instruments) Sample: Length 4cm x Width 0.5cm x Thickness 0.125cm Test length: 1cm Sample pretreatment: Keep at 23℃ and 50% relative humidity for 40 hours Test mode: Tensile Frequency: 1.6Hz (10rad / sec) Temperature range: 25~60℃ Heating rate: 1.5℃ / min Distortion range: 0.10% Initial load: 148g Measurement interval: 2 points / ℃

[0068] (Bending mode) In addition, the dynamic viscoelasticity of the same sample was measured in a bending mode under the following conditions: (Measurement conditions) Measurement device: RSA3 (manufactured by TA Instruments) Sample: Length 5cm x Width 0.5cm x Thickness 0.125cm Examiner :- Sample pretreatment: Keep at 23℃ and 50% relative humidity for 40 hours Test mode: Bending Frequency: 1.6Hz (10rad / sec) Temperature range: 25~60℃ Heating rate: 1.5℃ / min Distortion range: 0.10% Initial load:- Measurement interval: 2 points / ℃

[0069] 1 and 2 show plots of the storage modulus in the tensile mode and the bending mode for Example 1 and Comparative Example 1.

[0070] [Surface quality verification test] The polishing pad was placed at a predetermined position in the polishing device via a double-sided tape having an acrylic adhesive, and the Cu film substrate was polished under the following conditions. (polishing conditions) Polishing machine: F-REX300 (manufactured by Ebara Corporation) Disk: A188 (3M) Rotation speed: (table) 70 rpm, (top ring) 71 rpm Grinding pressure: 3.5psi Polishing agent temperature: 20℃ Abrasive discharge rate: 200ml / min Abrasive: PLANERLITE7000 (manufactured by Fujimi Corporation) Object to be polished: Cu film substrate Polishing time: 60 seconds Pad break: 35N 10 minutes Conditioning: Ex-situ, 35N, 4 scans

[0071] After the above polishing process, the polished surfaces of the 11th to 51st pieces were visually inspected for dot-like polishing scratches (microscratches) larger than 155 nm using a ReviewSEM eDR5210 (manufactured by KLA-Tencor Corporation), and the average value was obtained. The surface quality was evaluated based on the results of the scratches.

[0072] [Table 1] [Industrial Applicability]

[0073] The polishing pad of the present invention has industrial applicability as a polishing pad that can be used for polishing optical materials, semiconductor devices, substrates for hard disks, etc., and is particularly suitable for polishing devices having an oxide layer, a metal layer such as copper, etc. formed on a semiconductor wafer.

Claims

1. A polyurethane sheet is provided as the polishing layer, The polyurethane sheet had a storage modulus E' at 40° C. in dynamic viscoelasticity measurement performed under tensile mode conditions at a frequency of 1.6 Hz. T40 Storage modulus E' at 40°C in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz B40 The ratio of (E' B40 / E' T40 ) is 0.60 to 0.97; Polishing pad.

2. The storage elastic modulus E′ B40 But 1.50 x 10 8 ~4.50 x 10 8 Pa, 2. The polishing pad of claim 1.

3. The storage elastic modulus E′ T40 But 1.50 x 10 8 ~4.50 x 10 8 Pa, 3. The polishing pad according to claim 1 or 2.

4. The polyurethane sheet has a storage modulus E' at 50° C. in dynamic viscoelasticity measurement performed under bending mode conditions at a frequency of 1.6 Hz. B50 Storage modulus E' at 30 ° C. B30 The ratio of (E' B30 / E' B50 ) is 1.00 to 2.60; The polishing pad according to any one of claims 1 to 3.

5. The polyurethane sheet contains a polyurethane resin and hollow fine particles dispersed in the polyurethane resin. The polishing pad according to any one of claims 1 to 4.

6. The hollow fine particles have an average particle size of 30 μm or less. The polishing pad of claim 5.

7. A polishing step of polishing an object to be polished using the polishing pad according to any one of claims 1 to 6 in the presence of a polishing slurry. A method for manufacturing polished workpieces.

Citation Information

Patent Citations

  • Polishing pads for chemical mechanical planarization

    JP2004507076A

  • Polishing pad

    JP2005136400A

  • Optical device

    JP2010230911A

  • Abrasive pad and manufacturing method of the same

    JP2019177430A

  • Polishing pad and manufacturing method for polished work-piece

    JP2020055040A

Cited By

  • Polishing pads and polishing methods

    JP2026113391A